TW Hydrae: multi-wavelength interferometry of a transition disk. Issue Volume 8:Issue S299(2013) (6th January 2014) - Menu, J.; van Boekel, R.; Henning, T.; Benisty, M.; Chandler, C. J.; Linz, H.; Waelkens, C.; Andrews, S. M.; Calvet, N.; Carpenter, J. M.; Corder, S. A.; Deller, A. T.; et al.
Abstract: For over a decade, the structure of the inner "hole" in the transition disk around TW Hydrae has been a subject of debate. To probe the innermost regions of the protoplanetary disk, observations at the highest possible spatial resolution are required. We present new interferometric data of TW Hya from near-infrared to millimeter wavelengths. We confront existing models of the disk structure with the complete data set and develop a new, detailed radiative-transfer model. This model is characterized by: 1) a spatial separation of the largest grains from the small disk grains; and 2) a smooth inner rim structure, rather than a sharp disk edge.